THE EFFECT OF MINDFULNESS-BASED CLASSICAL GUIDANCE ON IMPROVING LEARNING MOTIVATION AMONG STUDENTS AT SMAN 7 SINJAI - Maykam, Mawaddatul; Saman, Abdul; Sinring, Abdullah (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to determine the effect of mindfulness-based classical guidance on increasing students' learning motivation at SMAN 7 Sinjai. This research employs an experimental method with a Non-Equivalent Control Group Design. The results indicate that mindfulness-based classical guidance has a significant positive impact on enhancing students' learning motivation. The distribution of students' motivation categories shows a greater shift towards high and very high categories in the experimental group, while the control group remains dominated by low and moderate categories. The t-test results show a significance level of 0.010 (< 0.05), indicating a significant difference between the experimental and control groups in terms of learning motivation after the intervention. The mindfulness approach has proven effective in helping students improve focus, emotional regulation, self-awareness, and academic stress management, all of which are essential components of learning motivation.